Efeitos da deficiência de tiamina e do processo de aprendizagem espacial sobre parâmetros neuroquímicos e imunológicos do hipocampo e tálamo de camundongos Swiss - Isabela Cristina Sena Romano (2019)
The experimental design of the present study allowed the evaluation of the effects of an episode of thiamine deficiency (TD) and training in a space navigation task (Learning process), on molecular components that are potential candidates to play a role in the phenomenon of cross talking between the Central Nervous System (CNS) and Immune System (IS). The central hypotheses were: (i) IS and CNS components are involved in the molecular mechanism of spatial learning and memory, and the involvement of these components depends on the stage of the learning process; and (ii) these molecular components can be altered by a neurodegenerative insult, such as the TD, which also affects the process of acquiring a spatial task. To test these hypotheses, 112 Swiss mice were used, divided into two groups: control and TD. After the TD episode, a 30-day recovery period was followed. Each group (control and TD) was subdivided into two: one subgroup was submitted to the shallow water maze (SWM) in order to solve it and the other was exposed to the STL without the animal performing the cognitive task. The training occurred during seven consecutive days. Immediately after training sessions 1, 3, 5, and 7, six animals from each subgroup were killed by decapitation and samples from the hippocampus and thalamus were separated and used for the determination, through biochemical methods, of the following neurobiological components: GABA, glutamate, Brain-Derived Neurotrophic Factor (BDNF), Interleukin 1-β (IL-1β), Tumor Necrosis Factor α (TNF-α) and Bdnf gene expression. The results show that TD affects GABA levels, glutamate/GABA rate, BDNF, Bdnf gene mRNA, TNF-α and Il-1β in both brain areas thalamus and hippocampus. Training in a spatial cognitive task has been found to be related to changes in GABA, BDNF, Bdnf gene mRNA and Il-1β levels in the hippocampus. Cognitive effort in the early and intermediate stages of the learning process is associated with changes in neuroimmunological components, which in turn are related to each other (i.e. GABA and BDNF) and to the individual's performance in the task acquisition. For the first time, it is demonstrated that neuroimmunological components of the hippocampus may be modulated during the performance of a spatial cognitive task and may be affected by neurodegenerative insults, such as TD.